ANALISIS KOMPONEN PERTUMBUHAN TENAGA KERJA SEKTOR PERTANIAN DI PROPINSIJAWA TENGAH (Pendekatan Model E-M Shift Share Analysis) - Ropingi Ropingi (Muhammadiyah University Press, 2002)
Economy development in Central Java is hardly apart from changes in the provision absorption of workers per economical sector, although it has been forwarded to decrease people's income distribution inequality. Therefore, the economy development should be focused on the efforts to distribute workers to economy sectors based on the relative market to Gross Regional Domestic Product (PDRB).In line with this problem, this research actually has some objectives. The first, to observe the allocation effects in agricultural and non-agricultural sectors in Central Java in the period 1995 - 1999. Secondly, to identify economy sectors at every regencies in Central Java. The required data here is time series data consisting the information about workers adapted from Central Statistics Agency (BPS) Central Java, and also completed by other supporting data. Meanwhile, to observe allocation effect, the writer apply E-M shift Share Analysis approach. Some findings has been achieved in this research, those are agricultural, manufacturing and service sectors which successfully absorb a large number of workers, identification on agricultural sector at several areas which have good fairly competition and the not ones, and also the friction moving of workers allocation from non-agricultural sectors into agricultural sectors.